Forensic Analysis on 52 Medical Malpractice Cases of Cardiac Death - Lu, J; Zhang, Y L; Luo, L (Fa yi xue za zhi, 2018)
To synthetically analyse the medical malpractice cases of cardiac death in forensic identification, and to explore the generality and characteristic of cause of death, medical malpractice and assessment of participation degree. Totally 52 medical malpractice cases of cardiac death examined in the Xiaoshan Branch Office, Hangzhou Minghao Forensic Judical Appraisal Institute, from January 2015 to April 2018 were collected. The general information of cases, medical institutions and situations of hospital stay, cause of death, medical malpractice and assessment of participation degree were retrospectively analysed. In 52 cases, the male to female ratio was 2.25:1, and most subjects aged >50-60. Cardiac death caused by hypertensive heart disease or coronary heart disease was most common （67.3%）, followed by viral myocarditis and cardiomyopathy （13.5%）. There were 24 cases involved surgery, and the survival time after surgery was from 1 h to 118 d with a 7 d medium value. There were 63 medical institutes involved in these medical malpractices. Medical malpractice presented in most hospitals more or less, and the participation degree was >20%-30%. Forensic appraisal contributes to determine causes of death, which not only provides scientific evidence for medical malpractice identification, but also improves diagnosis and treatment levels of medical institutions.